Festivals de musique québécois : où sont les femmes ? - Croteau, Laurianne (Ici Radio-Canada, 2019)
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; amériques; approches et analyses; arts; discipline; femmes* artistes; inégalités; musique; méthodologie; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

Reflets de la colonialité dans la scène des musiques nouvelles - Dharmoo, Gabriel (Intersections, 2019)
Certains membres de la scène des musiques nouvelles souhaitent en décentrer ses racines eurocentriques et en critiquer ses tendances colonialistes. Avant même de discuter des stratégies qui pourraient constituer un cadre décolonisateur, il est utile d’identifier comment la colonialité se reflète dans cette scène. L’auteur, lui-même membre actif de celle-ci, partage des pistes de réflexion portant sur l’homogénéité culturelle du milieu, les questions d’accès, l’héritage de la musique classique, le concept de l’excellence européenne, la présomption d’universalité, la coexistence de statuts de légitimité et de marginalité, la relation ambigüe avec l’appropriation culturelle et les fondements de l’attribution du mérite.
Keywords: DIG; EDI; amériques; approches et analyses; appropriation culturelle; art décolonial; arts; discipline; discours dominant; inégalités; musique; privilèges; québec; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

La masculinité à travers l’Atlantique : enjeux identitaires et musicaux dans Crépuscule du tourment 1 et 2 de Léonora Miano - Murray, Thomas (Études littéraires africaines, 2019)
L’oeuvre romanesque de Léonora Miano est profondément marquée par le recours à l’intermédialité. Celle-ci se met en place notamment grâce à des références constantes à une culture musicale qui dépasse l’axe France-Afrique structurant les identités afropéennes des personnages et ouvre l’univers fictionnel sur l’espace atlantique en faisant appel à un patrimoine musical essentiellement américain (jazz, funk, soul, etc.). Au-delà de l’aspect structurel de cette intermédialité musicale, sa présence diégétique renforce par bien des aspects la réflexion – de l’auteure et de ses personnages – d’une part sur les questions identitaires, d’autre part sur la masculinité et la position du « garçon noir » pris en étau entre divers schémas contraignants. Le présent article étudie cette articulation entre intermédialité musicale et identités dans les deux tomes de Crépuscule du tourment.
Keywords: DIG; afrique; approches et analyses; arts; discipline; europe; intermédialité; inégalités; littérature; masculinité; musique; ressource en ligne; régions géographiques; systèmes d'oppressions; études littéraires

Their own agenda: The history, development, and culture of women's orchestras outside the united states - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; approches et analyses; arts; discipline; femmes* musiciennes; genre; histoire des femmes*; histoire et politique; inégalités; musique; mémoires/thèses; périodes historiques; ressource en ligne; systèmes d'oppressions; thématiques

Blues et féminisme noir - Davis, Angela (Hors collecion, 2017)
Blues et féminisme noir explore l’œuvre de deux blueswomen quelque peu oubliées : Gertrude « Ma » Rainey (1886-1939) et Bessie Smith (1894-1937). La première incarne le blues traditionnel, la seconde, le blues classique. Dévalorisée par les spécialistes du blues et du jazz – qui sont en général des hommes blancs –, l’œuvre de ces chanteuses porte un message spécifique : elle affirme la place et les revendications d’autonomie des femmes noires américaines. En analysant et en contextualisant les paroles de leurs chansons, Davis met en évidence les prémices du féminisme noir et les signes avant-coureurs des grandes luttes émancipatrices à venir. Elle montre que Ma Rainey et Bessie Smith furent les premières rock stars de l’histoire de la musique : or elles étaient noires, bisexuelles, fêtardes, indépendantes et bagarreuses. Elles posèrent les bases d’une culture musicale qui prône une sexualité féminine libre et assumée, qui appelle à l’indépendance et à l’autonomie des femmes aux lendemains de la période esclavagiste, en revendiquant avec détermination l’égalité de « race » et de genre. Cette réflexion s’étire aux années 1940 en évoquant l’œuvre de Billie Holiday (1915-1959). Angela Davis réhabilite la conscience sociale de cette chanteuse d’envergure, trop souvent présentée sous le simple prisme des turpitudes de sa biographie. Blues et féminisme noir propose une histoire féministe et politique de la musique noire des années 1920 aux années 1940.
Keywords: 1900-1999; 1920-1929; 1930-1939; 1940-1949; DIG; afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; féminismes noirs; histoire; inégalités; militance; musique; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis; études culturelles

Bilan et perspectives sur la situation des compositrices au Québec : vers un décloisonnement des identités - Tremblay, Vicky (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Dans le domaine de la création musicale au Québec, les compositrices sont toujours moins nombreuses que les compositeurs. Si le métier de compositeur a du mal à être reconnu dans la société québécoise, les compositrices sont doublement marginalisées. Nombre d’entre elles témoignent des défis auxquels elles doivent faire face lorsqu’il est question de s’intégrer au milieu musical, et plusieurs musicologues ont tenté de mieux saisir — pour éventuellement résoudre — les problématiques particulières aux femmes dans le domaine de la composition. Cet article présente une conjonction entre les recherches sur les compositrices québécoises et des ouvrages aux fondements de la musicologie féministe aux États-Unis. Il discute de certaines problématiques communes aux compositrices de musique occidentale de tradition classique, pour finalement observer la fluidité des pratiques de certaines compositrices québécoises, qui inscrivent leurs démarches de création en dehors des « binarismes ». Au fil du temps, les femmes ont été marginalisées au sein des institutions dédiées à la musique de création. Ignorées par les critiques et rejetées par les programmes d’enseignement, elles ont longtemps été en réaction à cette marginalisation. Le rôle des institutions d’enseignement actuelles serait donc d’offrir un enseignement critique du canon musical tel qu’enseigné traditionnellement, pour mieux réintégrer ceux et celles qui en ont été rejetés. Si une ouverture se crée depuis quelques années vers des pratiques plus fluides, un décloisonnement de l’identité de compositrice et de compositeur s’observe déjà chez certaines compositrices qui éloignent leurs pratiques des « binarismes », notamment avec Danielle Palardy Roger, Diane Labrosse et Joane Hétu — pionnières du courant actualiste —, mais aussi avec des compositrices telles que Nicole Lizée et Katia Makdissi-Warren.
Keywords: DIG; LGBTQIA2+; amérique du nord; amériques; approches et analyses; arts; canada; discipline; femmes* artistes; genre; identités LGBTQIA2+; inégalités; musique; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; systèmes éducatifs; thématiques; travail

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

“Oh what a world”: Queer Masculinities, the musical construction of a reparative cultural historiography, and the music of Rufus Wainwright - Schwandt, Kevin C. (Université du Minnesota, 2010)
Throughout his ascendancy in fame and cultural visibility, singer/songwriter and gay pop icon Rufus Wainwright's output has been consistently related, by scholars and critics alike, to camp aesthetics, modes of artistic expression typically understood as emerging from queer communities, particularly certain gay male populations, but ones whose political potential is highly contested. Traditional conceptions of camp, as most famously articulated by Susan Sontag in the 1960s, emphasize style over content, necessarily rendering it politically-disengaged. However, scholars have vehemently challenged conceptions like Sontag's, in order to reclaim camp as a potent means to facilitate queer world-making and a powerful resistance to heteronormativity. I examine Wainwright's image and music in order to theorize a new queer interpretive listening position. Specifically, I draw upon the literary perspective of “reparative reading,” articulated by Eve Kosofsky Sedgwick in opposition to what she describes as “paranoid reading,” to propose a uniquely queer approach to musical and cultural historiography, exemplified by Wainwright's music. Much of the current queer musicology focuses on lost histories, systematic marginalization, and the commoditization of queer identities. While such approaches have produced important insights, thorough examination of the relationships between queer cultural products and their queer reception has proven elusive. This project suggests a unique approach to understanding the musical construction of a specific kind of queer masculinity, one which combines authorial creation with reparative conceptions of reception, in order to theorize a uniquely gay male interpretive position. When viewed through a theoretical lens combining politically-potent conceptions of camp performativity with a reparative reading position, Wainwright's music strikingly enacts Philip Brett's call to claim, not historical evidence, but the right of interpretation, emerging as an act of resistance via the reclamation and consolidation of a queer interpretive authority. In this way, Wainwright articulates both a rupture in the history of queer masculinity and a powerful means of resistance to the often-exclusionary relationships between literary, musical, and artistic objects and the heteronormative cultural systems in which they are created.
Keywords: 2000 à aujourd'hui; 2000-2009; DIG; LGBTQIA2+; approches et analyses; arts; culture populaire; discipline; historiographie; hétérosexisme; identités LGBTQIA2+; masculinité; musique; mémoires/thèses; périodes historiques; queer; ressource en ligne; résistance; systèmes d'oppressions; thématiques